Competitive Fixed-Bed Adsorption of Pb(II), Cu(II), and Ni(II) from Aqueous Solution Using Chitosan-Coated Bentonite - Wan-Chi Tsai; Mark Daniel G. de Luna; Hanna Lee P. Bermillo-Arriesgado; Cybelle M. Futalan; James I. Colades; Meng-Wei Wan (International Journal of Polymer Science)
Fixed-bed adsorption studies using chitosan-coated bentonite (CCB) as adsorbent media were investigated for the simultaneous adsorption of Pb(II), Cu(II), and Ni(II) from a multimetal system. The effects of operational parameters such as bed height, flow rate, and initial concentration on the length of mass transfer zone, breakthrough time, exhaustion time, and adsorption capacity at breakthrough were evaluated. With increasing bed height and decreasing flow rate and initial concentration, the breakthrough and exhaustion time were observed to favorably increase. Moreover, the adsorption capacity at breakthrough was observed to increase with decreasing initial concentration and flow rate and increasing bed height. The maximum adsorption capacity at breakthrough of 13.49 mg/g for Pb(II), 12.14 mg/g for Cu(II), and 10.29 mg/g for Ni(II) was attained at an initial influent concentration of 200 mg/L, bed height of 2.0 cm, and flow rate of 0.4 mL/min. Adsorption data were fitted with Adams-Bohart, Thomas, and Yoon-Nelson models. Experimental breakthrough curves were observed to be in good agreement (R2>0.85 and E%<50%) with the predicted curves generated by the kinetic models. This study demonstrates the effectiveness of CCB in the removal of Pb(II), Cu(II), and Ni(II) from a ternary metal solution.